2021
DOI: 10.1590/fm.2021.34122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peripheral arterial disease and associated factors in people with type 2 diabetes

Abstract: Introduction: The high rate of diabetes mellitus index (DM), along with the increase in cardiovascular compromise that DM favors, and the scarcity of epidemiological data regarding the prevalence of peripheral arterial disease (PAD) in this population, make it important to study risk factors associated with the development of PAD in the population with type 2 diabetes mellitus (DM2). Objective: To estimate the prevalence of PAD together with the associated factors in a sample of patients with DM2, treated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Patients in the second group were also associated with elevated mean serum blood glucose values (114.18 ± 38.35 mg/dL vs. 130.65 ± 65.35 mg/dL, p = 0.013), which is a predictor with a negative impact on the risk of developing potential vascular complications. Prospective studies to date have shown that half of patients with diabetes will develop PAD within 30 years of diagnosis, with reduced glomerular filtration rate, female gender, and the need for concomitant insulin therapy and oral antidiabetic drugs being among the main associated risk factors [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the second group were also associated with elevated mean serum blood glucose values (114.18 ± 38.35 mg/dL vs. 130.65 ± 65.35 mg/dL, p = 0.013), which is a predictor with a negative impact on the risk of developing potential vascular complications. Prospective studies to date have shown that half of patients with diabetes will develop PAD within 30 years of diagnosis, with reduced glomerular filtration rate, female gender, and the need for concomitant insulin therapy and oral antidiabetic drugs being among the main associated risk factors [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%